Plasma matrix metalloproteinases (MMP-2 and MMP-9) as prognostic biomarkers in coronary heart disease - MARYNENKO, Tetiana; HALENOVA, Tetiana; RAKSHA, Nataliia; VOVK, Tetiana; TYRAVSKA, Yuliya; SAVCHUK, Olexii; FALALYEYEVA, Tetyana; FAGOONEE, Sharmila; ABENAVOLI, Ludovico; OSTAPCHENKO, Liudmyla (Minerva Biotechnology and Biomolecular Research, 2022)
BACKGROUND: One of the major challenges in clinical practice on the management of heart failure is to predict the clinical evolution from common light symptoms to severe cardiovascular events. An association between the inflammatory processes, matrix metalloproteinases (MMPs) production and activation under cardiovascular disease has been reported. In a prospective study we assessed the levels of circulating MMP-2 and MMP-9 in patients with coronary heart disease (CHD), in correlation with some inflammatory parameters, including interleukin-6 (IL-6) and tumor necrosis factor alpha (TNF-α). METHODS: Our study included forty-three patients with different forms of CHD, such as stable angina (N.=18), unstable angina (N.=15), and myocardial infarction (N.=10). Plasma levels of MMP-2 and MMP-9 gelatinases were evaluated by immunoassay, while their activities were analyzed by means of SDS-PAGE with gelatin as a substrate. RESULTS: Our results revealed that MMP-2 as well as MMP-9 plasma levels, significantly increased only in patients with myocardial infarction, the more severe form of CHD. On the other hand, MMP-9 proteolytic activity was elevated in all groups of CHD patients, while, increased MMP-2 activity was associated with myocardial infarction. We observed a strong positive correlation between plasma levels of studied proteolytic enzymes and those of proinflammatory cytokines, such as IL-6 and TNF-α. CONCLUSIONS: Based on the results obtained we can hypothesize that MMP-9 might be a promising biomarker to identify CHD patients in the early stage of disease, while MMP-2 is more predictable in case of CHD clinical evolution to the more severe form. Further studies are required to confirm relationships between MMPs and the risk of cardiovascular diseases and to explore the involvement of MMPs in atherosclerosis plaque destabilization or cardiac remodeling processes.